2005
DOI: 10.1103/physrevlett.95.010503
|View full text |Cite
|
Sign up to set email alerts
|

No Signaling and Quantum Key Distribution

Abstract: Standard quantum key distribution protocols are provably secure against eavesdropping attacks, if quantum theory is correct. It is theoretically interesting to know if we need to assume the validity of quantum theory to prove the security of quantum key distribution, or whether its security can be based on other physical principles. The question would also be of practical interest if quantum mechanics were ever to fail in some regime, because a scientifically and technologically advanced eavesdropper could per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1,032
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 871 publications
(1,035 citation statements)
references
References 15 publications
3
1,032
0
Order By: Relevance
“…It guarantees that, for instance, pairs of photons can be treated as individual objects with individual properties and without any hidden correlations to other pairs. These, and many other results, addressed a number of subtleties and, finally, twenty years after its inception, the original entanglement-based key distribution protocol 7 has been shown to offer security even if the devices are not fully trusted and are exposed to noise 15,16,17,18,19,20 . This is assuming that quantum theory is all that there is, and that Eve is bound by the laws of quantum physics.…”
Section: Practicalitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…It guarantees that, for instance, pairs of photons can be treated as individual objects with individual properties and without any hidden correlations to other pairs. These, and many other results, addressed a number of subtleties and, finally, twenty years after its inception, the original entanglement-based key distribution protocol 7 has been shown to offer security even if the devices are not fully trusted and are exposed to noise 15,16,17,18,19,20 . This is assuming that quantum theory is all that there is, and that Eve is bound by the laws of quantum physics.…”
Section: Practicalitiesmentioning
confidence: 97%
“…Barring this, once the devices pass a certain statistical test they can be purchased without any knowledge of their internal working. This is a truly remarkable feat, also referred to as 'deviceindependent' cryptography 14,15,16,17,18,19,20 . Needless to say, proving security under such weak assumptions, with all the mathematical subtleties, is considerably more challenging than in the case of trusted devices, but the rapid progress in the past few years has been very encouraging, making device-independent cryptography one of the most active areas of quantum information science.…”
mentioning
confidence: 99%
“…BHK showed [4] how nonlocal correlations can be used as the basis of a key distribution scheme that is secure against nonsignaling eavesdroppers. Nonlocal correlations can also be used to give at least partial security against nonsignaling eavesdroppers in more practical quantum key distribution schemes [17,18].…”
Section: Is a Prl 97 170409 (2006) P H Y S I C A L R E V I E W L E Tmentioning
confidence: 99%
“…For example, the nonlocality of quantum correlations allows communication complexity problems to be solved using an amount of communication that is smaller than is possible classically [3]. Barrett-Hardy-Kent (BHK) recently showed that testing particular nonlocal quantum correlations allows two parties to distribute a secret key securely, in such a way that the security is guaranteed by the no-signaling principle alone [4] (i.e., without relying on the validity of quantum theory).…”
mentioning
confidence: 99%
“…Quantum mechanics has been tested experimentally for nearly a century, to very high precision. But even if quantum mechanics is superseded by a new physical theory, it is not necessarily true that quantum key distribution would be insecure: for example, secure key distribution can be achieved in a manner similar to QKD solely based on the assumption that no faster-than-light communication is possible [BHK05].…”
Section: The Security Of Qkdmentioning
confidence: 99%